Facile synthesis of N/B-double-doped Mn2O3 and WO3 nanoparticles for dye degradation under visible light. Issue 18 (10th August 2020) - Shah, Jafar Hussain; Fiaz, Mohammad; Athar, Muhammad; Ali, Jafar; Rubab, Mahnoor; Mehmood, Rashid; Jamil, Syed Umair Ullah; Djellabi, Ridha
ABSTRACT: In the present work, nitrogen-doped and nitrogen–boron-double-doped manganese oxide (Mn2 O3 ) and tungsten oxide (WO3 ) nanoparticles were synthesized using precipitation-hydrothermal method for methylene blue degradation under visible light. Materials were characterized using X-ray diffraction (XRD) analysis, Scanning electron microscopy, Energy dispersive X-ray spectroscopy and UV-vis spectroscopy. Results showed that N and B were successfully incorporated into the crystal lattices of Mn2 O3 and WO3 . XRD showed that WO3 was crystallized in the form of a monoclinic lattice, while cubic Mn2 O3 was produced in the cubic form. The crystallite size was found to be decreased due to the substitution of N and B elements which reveals their roles to accelerate the crystal nucleation rate resulting in the decreased size. On the other hand, single and double doping has successfully narrowed the band gaps of the as-synthesised metal oxide photocatalysts resulting in better absorption in the visible light. Band gaps obtained were as follows: 3.02, 2.50, 1.73 and 1.77 eV for N–WO3 N/B–WO3, N–Mn2 O3 and N/B–Mn2 O3 respectively. Photocatalytic experiments showed that all as-synthesised materials exhibited a photocatalytic efficiency under visible light ≥420 nm. The degradation efficiency of methylene blue (MB) was in the following order: N–B-co-doped metal oxides > N-doped metal oxides > metal oxides. The presence of scavenger molecules such as isopropanol, EDTA-2Na and benzoquinone inhibited MB degradation. Finally, the results showed that these materials can be reused several times without a notable decrease in efficiency. GRAPHICAL ABSTRACT: UF0001